Productive and reproductive performance of broiler breeder laying hens as affected by dietary levels either of l-carnitine or herbal mixture - Abdel-Rahman, S. A.; Abou-Ashour, A. M.; Abousekken, M. S. M.; EI-Fiky, A. A.; EI-Adawi, M. A. (2008)
A total number of four hundred and sixty two Ross 308 broiler breeder hens (40-wks of age) were used to evaluate the effect of dietary supplemented L-camitine (LC) and herbal mixture (HM) on laying hens productive and reproductive performance , egg quality measurements, blood parameters and microbiological status . Hens were randomly distributed into 7 treatments each in 3 replicates (20 hens and 2 cocks per each replicate) and housed in floor pens. Feed was restricted according 10 the breed instruction ,while water was supplied ad-libitum, All hens were kept under the same managerial, hygienic and environmental conditions throughout the experimental period (12 weeks ). Com-soybean meal basal diet was formulated to cover the nutrients requirements recommended for the breed and served as the control diet (Tb7(B) ; 3 supplemented levels of L-camitine (LC) (10,20 and 30 mg /kg) (or Tb1(B,Tb2 (Band Tb3(B, respectively and 3 other supplemented levels of herbal mixture (HM) 5,10 and 15 g/kg for Tb4(B,Tb5 (Band Tv, respectively. Initial body weight, final body weight ,body weight change, egg production, egg weight, egg mass, feed conversion ratio, hatchability % , hatching of fertile eggs, hatching weight , egg quality and composition were also determined. Blood parameters, microbiological study were also determined and economical efficiency was calculated The results indicated that: 1. Groups fed diet supplemented with 15 g/kg HM significantly (P<0.05)improved final live body weight, egg production rate ,total egg production, mean egg weight ,egg mass and daily egg mass more than groups either fed diet supplemented with L-camitine or control group. 2. Addition HM to hen diets significantly improved feed conversion rate (FCR) fertility rate, hatchability rate and % hatchability of fertile eggs , while decreased embryonic early and late dead compared to L-carnitine supplemented diets. 3. Supplementation of dietary herb mixture for laying hen diets significantly improved the antioxidant capacity, Ca and P while decreased LDL,HDL, total cholesterol, triglycerides and total lipids in blood plasma. 4. Combination of 15 g/kg herbal mixture in laying hen diet showed significantly more improvements in external and internal egg quality than L-carnitine supplemented diet. 5. Total bacterial Count (TBC) of cloaca swabs from laying hens fed HM groups was significantly lower than those of LC groups, which led to improvements in fertility% and hatchability of these eggs. 6. Further studies must be carried out to study the possibility of using natural antioxidant in commercial broiler breeder diets for long time during laying period. It may be concluded from this study and from economical point of view that supplementation of 15g/kg of herbal mixture (HM) as a natural antioxidant to broiler breeder laying hen diets during 40-52 weeks of age improved their productive and reproductive performance than artificial antioxidants.s
Includes references.
Summary in Arabic.
1
Keywords: Hens -- Feeding and feeds; Hens -- Production; Hens -- Reproduction; Carnitine; Eggs -- Quality